Option pricing with GOU process under a stochastic earning yield - Phewchean, Nattakorn (Curtin University, 2012)
The aim of this research is to study and extend the Black-Scholes model framework. The research consists of three parts. The first part is to derive the Black-Scholes type models under different application perspective. The second part is to develop a European option pricing model taking into account stochastic earning yield. The third part is to validate the new option price model. Numerical simulation results show that our new model out-performs others.